Numerical study of vibrations in the milling process - Pereira, Ana I. (2019)
Nowadays there is a great need to increase productivity along with high quality levels, which constitutes a major challenge to the industry and engineering development. In spite of the existence of advanced equipment capable of mass producing with great precision and performance such as CNC machines, some vibration induced issues may appear during the machining process that need to be addressed. The present research is based on a study of the dynamic behaviour of a milling CNC machine to identify and optimize vibration-sensitive parameters values (cutting speed, feed, axial penetration and radial penetration) in order to reduce the effect of chatter in milling process. Initially, the theoretical basis of milling operation is presented. Then, the response surface method (RS) and Genetic Algorithms (GA) are used to optimize the milling parameters. Based on the results obtained, it was possible to identify optimal parameters to minimize machining vibration.